(untitled) (JKPD Banten - Jurnal Kebijakan Pembangunan Daerah Provinsi Banten, 2025)
Hypertension is one of the main causes of non-communicable diseases that can reduce the quality of life in the community. To prevent hypertension, serious attention is needed and the role of health cadres is very important. This study aims to examine the contribution of health cadres in preventing hypertension in East Belitung Regency. The method used in this study is a qualitative descriptive approach. This approach aims to obtain in-depth information related to the role of health cadres in the hypertension prevention and control program in the East Belitung Regency health center area. Health cadres in the community have responsibilities including as coordinators, community mobilizers, monitors, health promotion, providing basic assistance, and documenting activities. The results of the study showed that several factors that influence the role of health cadres in efforts to prevent hypertension include supporting factors such as knowledge and attitudes, reinforcing factors in the form of behavior, support from the village government and family, and enabling factors including health services and access to health services. In carrying out their role, the usefulness of health cadres in preventing hypertension can be divided into three categories, namely primary prevention which includes data collection, health education, and health screening; secondary prevention which includes identification of individuals with risk factors for non-communicable diseases and measurements for early detection; and tertiary prevention which provides support to communities to undergo regular health checks and receive treatment.